2011
DOI: 10.2478/v10145-011-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Changes in the Ichthyofauna of Latvia's Inland Waters

Abstract: Changes in the ichthyofauna of Latvia's inland waters and their causes have been analyzed. Information about the distribution and occurrence of fish, obtained from various sources of literature, official reports, "BIOR" data bases on fishery statistics, as well as field research done from 1990 to 2010, has been collected and compared. Anthropogenic activity in the 20th century, such as rivers blocking by dams and fish introduction and acclimatization, has affected ichthyofauna more significantly. Keywords-Latv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In Estonia, the species is listed as EN (Lilleleht, ). In more southern areas around the Baltic Sea the situation is more positive with stable or increasing populations, although it may be difficult to separate effects of natural processes from past stocking programmes (Aleksejevs & Birzaks, ). In parts of Germany, the number of wels has even increased to such a degree that the species is presently regarded as a pest; moreover, illegal introductions across southern and western Europe have in recent time greatly increased the number of invasive populations (Cucherousset et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In Estonia, the species is listed as EN (Lilleleht, ). In more southern areas around the Baltic Sea the situation is more positive with stable or increasing populations, although it may be difficult to separate effects of natural processes from past stocking programmes (Aleksejevs & Birzaks, ). In parts of Germany, the number of wels has even increased to such a degree that the species is presently regarded as a pest; moreover, illegal introductions across southern and western Europe have in recent time greatly increased the number of invasive populations (Cucherousset et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…If the sediments are polluted, toxic chemicals such as heavy metals and other pollutants can release back into the water. In addition to changes of water flow, also impact to the fish fauna can be observed, in deeper lakes the area is more accessible to larger predators, not only small fish [22].…”
Section: Resultsmentioning
confidence: 99%
“…Studies in Latvia showed that the distribution and abundance of cold-and warm-water FWsp have changed from the Palaeolithic to the present, with a general increase in the distribution of some warmwater species (Sloka 1970, 1988, Aleksejevs & Birzaks 2011). Climate change is apparently linked to the periodical mass die-off of cold-water species in Latvian lakes and changes in the migration patterns of diadromous species in rivers (Aleksejevs & Birzaks 2011, Aleksejevs & Birzaks 2012, Birzaks 2020). In the past, species adapted to climate change by shifting their distribution to colonize suitable habitats.…”
Section: Discussionmentioning
confidence: 99%